Management of the urethra in urothelial bladder cancer - Kanaroglou, Androniki; Shayegan, Bobby (Canadian Urological Association Journal, 2013)
The standard of care in the management of invasive urothelial cancer of the bladder is radical cystectomy and pelvic lymphadenectomy. Although uncommon, recurrence of disease in the retained urethra following cystectomy carries a poor prognosis. The need for assessment of risk of recurrence is greater now than ever with wider adoption of orthotopic bladder substitution. This review will address the contemporary management of the urethra following cystectomy for urothelial cancer.